Consumer Behavior in the Digital Marketplace: A Fuzzy Evaluation Approach - Zhan , Wenxi (Transactions on Economics, Business and Management Research, 2024)
With the growing prevalence of the internet and the development of logistics, consumers face increasingly complex choices when shopping online. Therefore, this article introduces fuzzy comprehensive evaluation to address these shopping issues. In analyzing consumers' purchase decision-making problems for online shopping, it is essential to subjectively evaluate products, such as price, quality, and reputation. By constructing fuzzy relationships and assigning weights, this method effectively handles the ambiguity and uncertainty of evaluation information, reflecting consumers' subjective preferences in actual shopping decisions. This study concludes that quality is the dominant factor among numerous commodity factors,and it also established a shopping decision model, which aids consumers in making the best decisions during their shopping, thereby enhancing shopping efficiency and satisfaction. The results indicate that compared to traditional methods, this method can more accurately focus on consumer purchase intention and improve the understanding of shopping decisions. The paper summarizes the fuzzy comprehensive evaluation of its application value in shopping problems, pointing out that it can better simulate human fuzzy decision-making processes and provide a more practical shopping decision assistance tool. This study not only enriches the application of fuzzy comprehensive evaluation theory in consumer behavior research, but also provides consumers with a scientific and practical shopping decision support method.